RESILIENSI DAN EMOTIONAL EXHAUSTION PADA IMAM KATOLIK KEUSKUPAN AGUNG MERAUKE: ANALISIS HUBUNGAN DALAM KONTEKS PELAYANAN PASTORAL - Amelwatin, Theodorius; Batmomolin, Anastasia M D (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2026)
Pastoral ministry requires Catholic priests to be intensively involved in accompanying the faithful, making moral decisions, and managing various administrative responsibilities. These demands often increase the risk of emotional exhaustion, which is a core component of burnout and negatively affects both the quality of ministry and priests’ psychological well-being. This study aims to examine the relationship between resilience and emotional exhaustion among Catholic priests in the Archdiocese of Merauke. Employing a quantitative approach with a survey design, data were collected online using Google Forms. A convenience sampling technique was applied, resulting in the participation of 58 respondents. The data were processed and analyzed using the Statistical Package for the Social Sciences (SPSS) version 27. The results indicate that resilience has a significant negative relationship with emotional exhaustion, meaning that higher levels of resilience are associated with lower levels of emotional exhaustion among priests. These findings underscore the importance of strengthening psychological resilience as a preventive strategy against burnout in pastoral ministry. Practical implications include the need for accompaniment programs, resilience training, and systemic support from the diocese to sustain priests’ ministry and enhance their holistic well-being.